2011
DOI: 10.2337/db09-1156
|View full text |Cite
|
Sign up to set email alerts
|

Defective Glycogenesis Contributes Toward the Inability to Suppress Hepatic Glucose Production in Response to Hyperglycemia and Hyperinsulinemia in Zucker Diabetic Fatty Rats

Abstract: OBJECTIVEExamine whether normalizing net hepatic glycogenesis restores endogenous glucose production and hepatic glucose phosphorylation in response to diabetic levels of plasma glucose and insulin in Zucker diabetic fatty rats (ZDF).RESEARCH DESIGN AND METHODSHepatic glucose and intermediate fluxes (µmol ⋅ kg−1 ⋅ min−1) were measured with and without a glycogen phosphorylase inhibitor (GPI) using [2-3H]glucose, [3-3H]glucose, and [U-14C]alanine in 20 h-fasted conscious ZDF and their lean littermates (ZCL) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…GP activity is responsive to hepatic levels of glucose 6-phosphate, with a suppression of activity in response to higher glucose 6-phosphate concentrations, and thus the relative GP activities in the two groups are consistent with their relative rates of NHGU. GP activity under hyperglycemic and hyperinsulinemic conditions has previously been shown to be increased in drug-induced and genetic rodent models of obesity and/or diabetes (7,41,48), but not in high-fat-fed rats (30). In the HFD, HFrD, and HFFD groups in our previous studies (10,12), GP showed a tendency to be elevated relative to the controls.…”
Section: Liver Tissue Datamentioning
confidence: 51%
“…GP activity is responsive to hepatic levels of glucose 6-phosphate, with a suppression of activity in response to higher glucose 6-phosphate concentrations, and thus the relative GP activities in the two groups are consistent with their relative rates of NHGU. GP activity under hyperglycemic and hyperinsulinemic conditions has previously been shown to be increased in drug-induced and genetic rodent models of obesity and/or diabetes (7,41,48), but not in high-fat-fed rats (30). In the HFD, HFrD, and HFFD groups in our previous studies (10,12), GP showed a tendency to be elevated relative to the controls.…”
Section: Liver Tissue Datamentioning
confidence: 51%
“…The properties and capacity of the liver's GLUT2 are such that glucose transport across the plasma membrane depends on its concentration gradient, and therefore, it is not a regulatory step in determination of hepatic glucose flux (29,41). The catalytic activity of GK is not affected by its product (G-6-P) (32), and indeed, GK flux is not altered by a change in the G-6-P level resulting from a change in flux of the downstream pathways (44). Therefore, the improvement of the liver's ability to suppress glucose production and store glucose as glycogen in response to the rise in plasma glucose achieved by correcting hyperglycemia was due to normalized acceleration of glucose phosphorylation that might relate to maintenance of GK protein expression and normalization of GK translocation in response to hyperglycemia.…”
Section: Discussionmentioning
confidence: 96%
“…We measured glycogen synthase activity and phosphorylase activity, glycogen and glucose 6-phosphate (G-6-P) in liver, plasma levels of glucose, free fatty acids (FFAs), triglyceride, insulin, and glucagon, corticosterone, blood levels of hemoglobin A1c, lactate, and alanine, urinary glucose, specific activities of [ (15,16,44). Triglyceride content in liver, soleus muscle, and gastrocnemius muscle were determined according to the method of Carr et al (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations